1997
DOI: 10.1021/es970113r
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of 137Cs and K in Soil Solution Predict the Plant Availability of 137Cs in Soils

Abstract: The plant availability of 137 Cs in soils varies widely between soil types. The source of this variation was analyzed in a pot trial. Thirty topsoils covering a wide range in textural classes were contaminated with 137 Cs and incubated for 41 days prior to 19 days plant growth. The plant-soil 137 Cs concentration ratio (TF) varied from 0.002 to 2.6 g g -1 between soils. The soil-soil solution 137 Cs concentration ratio (K D ) varied from 123 to 167 000 mL g -1 between soils. The log TF was negatively correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
77
4

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(89 citation statements)
references
References 21 publications
8
77
4
Order By: Relevance
“…So we witness for a K concentration range of 3.6 to 0.17 mM an exact compensation between CF and : lowering [K] leads to an increase in Kq which is exactly paralleled by a linear increase in CF, resulting in an invariance in TF. Similar conclusions were formulated just recently [13] …”
Section: Soil-plant Transfersupporting
confidence: 89%
“…So we witness for a K concentration range of 3.6 to 0.17 mM an exact compensation between CF and : lowering [K] leads to an increase in Kq which is exactly paralleled by a linear increase in CF, resulting in an invariance in TF. Similar conclusions were formulated just recently [13] …”
Section: Soil-plant Transfersupporting
confidence: 89%
“…moles dm" 3 ) as observed experimentally by [12] Smolders et al (1997). Data presented by [12,13] indicated a relationship between RIP and clay content, so that IBR and RIP (radiocaesium interception potential) can be used to estimate a soil Ka value; Kd may then be used to estimate soil solution radiocaesium concentration in conjunction with CF in order to predict plant radiocaesium activity. As the value of ms for a soil is unlikely to be recorded in spatial data sets, it is necessary to estimate this soil property within the model.…”
Section: The Semi-mechanistic Dynamic Transfer Modelsupporting
confidence: 79%
“…However, these were pot experiments with artificial addition of 137 Cs, and few soil types were examined. Lembrechts (1993), Nisbet (1993) and Smolders et al (1997) reported K is most effective when K is deficient. Because most fields in Japan are well fertilized, the potential effectiveness of additional fertilization can be low.…”
Section: Introductionmentioning
confidence: 99%